Analisis Tren Perubahan Tekanan Darah Setelah Program Latihan Senam Hipertensi pada Orang Dewasa - Harliani Harliani; Muhammad Basri; Sukriyadi Adi (Celebes Health Journal, 2026)
Background: Hypertension remains a major public health problem and contributes substantially to cardiovascular morbidity and mortality. Non-pharmacological interventions, including structured physical exercise, are increasingly recommended as complementary strategies for blood pressure control. Hypertension exercise has been proposed as a feasible and low-cost approach; however, evidence regarding its clinical impact and response discrimination remains limited. Objective: This study aimed to evaluate changes in systolic and diastolic blood pressure following a hypertension exercise intervention and to assess the magnitude and discriminative performance of blood pressure reduction among adult participants. Methods: .This quasi-experimental study employed a single-group pre–post design to evaluate the effects of a hypertension exercise intervention on blood pressure. A total of 27 adult participants with elevated blood pressure were included. Systolic and diastolic blood pressure were measured before and after the intervention. Paired-sample t-tests were used to assess pre post differences. Effect sizes were calculated using Cohen’s d to determine the magnitude of change. Receiver Operating Characteristic (ROC) analysis was conducted to evaluate the ability of systolic blood pressure reduction to discriminate clinically meaningful responses ( 5 mmHg). Results: Following the intervention, mean systolic blood pressure decreased significantly, accompanied by a significant reduction in diastolic blood pressure (p <0.001 for both). Effect size analysis demonstrated a large effect for systolic blood pressure reduction and a moderate effect for diastolic blood pressure reduction. ROC analysis showed good discriminative performance, with a conservative area under the curve indicating that systolic blood pressure reduction was able to identify clinically meaningful responses. Conclusion: Hypertension exercise was associated with statistically and clinically meaningful reductions in blood pressure among adult participants. Although causal inference is limited by the quasi-experimental design, these findings support the potential role of hypertension exercise as a non-pharmacological strategy for blood pressure management. Further controlled studies with larger samples and longer follow up are warranted.